Система біометричного розпізнавання студентів у системі безпеки кіберуніверситету - Ситнік, Н. О. (ХНУРЕ, 2023)
This work examines the technology of biometric recognition of students at the university using biometric devices and a database system. Biometrics are a rapidly expanding and reliable form of authentication because physical characteristics are, for the most part, much more difficult to falsify than passwords or PINs. Additionally, the ubiquitous implementation of biometric scanners on popular consumer devices has made that much easier.